Integrasi Pendidikan Karakter pada Pembelajaran Tematik Tema 3 di MI Baiturrahman Sundul Parang Magetan - Dian Nafi Firdhaus (Jurnal Pendidikan Madrasah, 2021)
The problems experienced by the community today are increasingly complex and diverse, and have become entrenched in the community environment, especially regarding character education. The educational process that aims to educate and shape the human personality to be better provides challenges to a learning in the classroom with characteristics and problems brought by students. It is ironic to hear good news on TV, social media, the Internet, which shows unnatural behavior seen by students in school, especially in elementary school; Students who dare to beat their parents, speed on the highway, criminality, or even acts of violence either committed by students or their parents. Based on the statement, the implementation of character education to the learning process in MI becomes a must that must be done and applied, because it is considered able to make learners become smarter, and able to educate learners who have manners and character and make learners become useful individuals in their families or in the community. This study uses the ADDIE model's Development Research Method (R&D) with qualitative data analysis techniques (Miles and Haberman), because the topics raised by researchers relate to the development of "Character Education" Teaching Materials related to social problems or student behavior, and "Character Formation" in the learning process in schools/madrasah.